STRATEGI FINANCIAL LITERACY UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT INDUSTRI KAWASAN WISATA KABUPATEN GERSIK JAWA TIMUR - Ratnawati, Tri; Mujanah, Siti; Lokajaya, Nyoman (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to detect financial literacy and public welfare by factor analysis. The results show that the financial literacy has 12 important factors, namely, old age, financial education, financial experience, business financial budgeting, economic behavior, financial attitude, gender, financial behavior, self control, government policy, financial socialization from the government and family financial budgeting. Whereas the welfare factor of the community is the necessity of life and well-established economy. There are four pillars that must carry out both short-term and medium-term,long term finance, namely the government including bank and non-bank financial institutions, small-scale business enterprises, academics and medium and large-scale business actors in the effort to implement Corporate Social Responsibility  programs. Activities that can be carried out by academics are in the form of training assistance so that they can prepare financial reports and audit in the long term while the government facilitates access to capital, apprenticeship to medium and large scale industries, regulation of licensing facilities.